GUIDELINES FOR ENHANCING TEACHERS’ MORALE TO DEVELOP EFFECTIVE WORK RESULTS BY EDUCATIONAL INSTITUTION ADMINISTRATORS UNDER THE OFFICE OF VOCATIONAL EDUCATION SUPHANBURI PROVINCE - กลิ่นดีปลี กิตติศักดิ์; Tharwonkit, Somkul (Journal of MCU Phetchaburi Review, 2025)
Teacher morale and motivation are important factors that affect work performance, including teaching quality, workload, and efficient budget use. This research aimed to 1) study the level of morale enhancement of teachers by school administrators under the Office of Vocational Education, Suphanburi Province. 2) To study the level of performance development for efficiency by school administrators under the Office of Vocational Education, Suphanburi Province. 3) To present guidelines for enhancing teachers’ morale and motivation in order to develop effective work performance by school administrators under the Office of Vocational Education, Suphanburi Province. The sample was divided into 2 groups: 1) administrators, 6 people; 2) teachers, 184 people, totaling 190 people. The research instruments were questionnaires and interviews. The statistics used for data analysis were frequency, percentage, mean, and standard deviation. The research results found that 1) the level of morale and encouragement enhancement of teachers by school administrators, overall and in each aspect, was at a high level. 2) The level of development of work performance to be effective by the school administrators, overall and in each aspect, has good performance results in terms of work quality and time. 3) Guidelines for enhancing teachers’ morale and motivation to develop effective work performance by school administrators Create job security, adjust salary and promote welfare, and promote good relationships with supervisors and coworkers. Establish clear management policies, promote and support good working conditions, plan and improve work quality, reduce unnecessary workload, use technology in management, and promote the economical use of resources.